The relationship between motivation and work compensation with nurse performance - Wardani, Diah Sukma; Siregar, Santy Deasy; Siagian, Masryna; Perdani, Mustika Lili; Martono, Martono; Tanamal, Claudia; Fransisca, Wennie; Karen, Yulia (Buletin Kedokteran & Kesehatan Prima, 2025)
This study investigates the relationship between motivation, compensation, and nurse performance at Muyang Kute Hospital, Bener Meriah Regency, Indonesia, using an analytical survey with a cross-sectional design. A sample of 154 nurses was randomly selected from a population of 250. Data were collected via questionnaires measuring motivation, compensation, and performance, categorized as "good" or "poor." Bivariate analysis using the chi-square test revealed a significant association between both motivation and compensation with nurse performance (p < 0.05). Nurses with positive motivation and compensation demonstrated significantly better performance. Specifically, 98.1% of nurses with positive motivation and 94.9% with positive compensation exhibited good performance. These findings underscore the critical role of intrinsic and extrinsic factors in enhancing nurse performance, highlighting the need for strategies to improve motivation and ensure adequate compensation to optimize healthcare delivery.